Major Depressive Disorder Is Associated With Abnormal Interoceptive Activity and Functional Connectivity in the Insula - Avery, Jason A.; Drevets, Wayne C.; Moseman, Scott E.; Bodurka, Jerzy; Barcalow, Joel C.; Simmons, W. Kyle (Biological psychiatry (1969), 2014)
Somatic complaints and altered interoceptive awareness are common features in the clinical presentation of major depressive disorder (MDD). Recently, neurobiological evidence has accumulated demonstrating that the insula is one of the primary cortical structures underlying interoceptive awareness. Abnormal interoceptive representation within the insula may thus contribute to the pathophysiology and symptomatology of MDD. We compared functional magnetic resonance imaging blood oxygenation level-dependent responses between 20 unmedicated adults with MDD and 20 healthy control participants during a task requiring attention to visceral interoceptive sensations and also assessed the relationship of this blood oxygenation level-dependent response to depression severity, as rated using the Hamilton Depression Rating Scale. Additionally, we examined between-group differences in insula resting-state functional connectivity and its relationship to Hamilton Depression Rating Scale ratings of depression severity. Relative to the healthy control subjects, unmedicated MDD subjects exhibited decreased activity bilaterally in the dorsal mid-insula cortex (dmIC) during interoception. Activity within the insula during the interoceptive attention task was negatively correlated with both depression severity and somatic symptom severity in depressed subjects. Major depressive disorder also was associated with greater resting-state functional connectivity between the dmIC and limbic brain regions implicated previously in MDD, including the amygdala, subgenual prefrontal cortex, and orbitofrontal cortex. Moreover, functional connectivity between these regions and the dmIC was positively correlated with depression severity. Major depressive disorder and the somatic symptoms of depression are associated with abnormal interoceptive representation within the insula.